Determinantof Net Interest Margin in Indonesia Bank Moderated by Risk - Adler Haymans Manurung , Benny Hutahayan , Kevin Deniswara, Tipri Rose Kartika (International Journal of Advanced Science and Technology, 2020)
This paper aims to examine determinants of Net Interest Margin (NIM) in Indonesia’s Bank.  This research use model Panel data for period 2013 – 2018.  This research found that Financial Ratio of bank which is Operating Expenses to Operating Income, Market Power Risk and Asset significant affected Net interest margin. Fourth, Macroeconomic Variable which is Oil Price and Exchange Rate significantly affected Net Interest Margin.  Risk as moderating variable could be to strong or weak effect of CAR, BOPO, Total Asset, Oil Price, Exchange Rate and Economic Growth to affect Net Interest Margin. This finding research is quite different to previous finding research about variable independent does not be significant to affect dependent variable but it is significant through moderating variable. Keyword: Net Interest Margin, Non-Performing Loan, Risk, Asset, Market Power Capital Adequacy Ratio, Oil Price, Economic Growth, Exchange Rate, Moderating Variable.